Optimizing The Role Of Members In Increasing The Sales Of Campus Cooperative Business - Anggraeni, Fitria Nur (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
In Indonesia, the role of local businesses or business units established by a community has not proven successful, as business units built conventionally. Thus, often in increasing sales/profits, they use traditional methods, namely role optimization. Naturally, this simple technique is quite effective in maintaining the existence of business units, but in a broader and long term scope, it is necessary to apply a competitive business strategy. The purpose of this study is to analyze the optimization of the role of business unit members at a private university in South Tangerang. The research method used is descriptive quantitative, in which the research sample is based on numbers, in this case the financial statements are used as the basis for analysis and conclusion. The research data used is the financial reports of the Pamulang University campus business units in 2021. The results of the research show that the member role strategy is very effective for local business units on campus. Evidently, in the 2021 financial report, the largest number of purchases come from members, most of whom are campus lecturers and education staff. Thus, this strategy needs to be maintained with a good profit sharing scheme, so that a mutually beneficial cycle is built.